Anode catalyst layer optimization in polymer electrolyte membrane water electrolysis: Modeling catalyst layer properties and interface effects - Ma, Tien Ching; Hutzler, Andreas; Hanke-Rauschenbach, Richard; Thiele, Simon (Electrochemistry Communications, 2025)
The design of the anode catalyst layer (ACL) and its interface to the porous transport layer (PTL) significantly influence cell behavior of proton exchange membrane water electrolysis (PEMWE). To understand the complex interaction between the two layers and its interface on cell performance, modeling approaches are necessary. In this study, we present an efficient single-phase two-dimensional model resolving both in-plane and through-plane directions of the interface and the catalyst layer. It is validated both by experimental tomographic data and polarization curves. We find that the single-phase model describes polarization behavior well at low current densities. For higher current densities deviations can be found. While the model provides quantitative predictions for most cases, the absence of detailed two-phase flow modeling may limit its accuracy at high current densities where liquid-gas interactions become more dominant. For one sample showing larger deviations at higher potentials, we apply a simple two-phase model, which seems to explain the deviations. We apply the model to determine the optimal ACL/PTL interface configurations for ACLs with various electrical conductivities. The model reveals that a tenfold increase in electrical conductivity can result in a doubling of cell current density. By explaining interactions between ACL properties, ACL/PTL design and ACL performance, the model fosters to accelerate future optimization.
CRIS-Team Scopus Importer:2025-06-06
Keywords: 2D model; Catalyst utilization; Porous transport layer; Proton exchange membrane water electrolysis; PTL interface; Structure optimization